Exploring the Utilization of Plastic Sand in Construction to Drive Sustainable Practices and Foster a Circular Economy - Nnadikwe Johnson; Okure Unyime Enobong; Onyewudiala Ibeawuchi Julius; Stephen Oyelami (SEAN Institute, 2026)
This research explores utilizing waste plastics in construction to promote a circular economy and mitigate plastic waste's environmental footprint in Nigeria's urban centers. Innovative bricks made from low-density polyethylene bags and sand offer thermal and sound insulation properties, pollution control, and cost reduction. The eco-friendly bricks demonstrate beneficial properties: lightweight, porous structure, low thermal conductivity, and high mechanical strength comparable to conventional bricks.The experimental process involved combining cement, sand, and waste plastic/nylon (0-15% by weight) with fly ash, followed by underwater curing and baking. Results show compressive strengths of 19.5 MPa (0% waste), 19.46 MPa (5% waste), 20.3 MPa (10% waste), and 21.1 MPa (15% waste). The bricks exhibit reduced water absorption capacity (0.085-0.34%) and lower efflorescence values.The innovative bricks offer numerous benefits: enhanced strength and durability, reduced environmental impact, and economic value for manufacturers. They contribute to sustainable construction practices, reducing sand extraction and plastic waste accumulation. This research showcases the potential for eco-friendly bricks to enhance energy efficiency in buildings and promote a sustainable ecosystem for plastic waste management.